2021
DOI: 10.48550/arxiv.2111.00896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A scalable network model for electrically tunable ferroelectric domain structure in twistronic bilayers of two-dimensional semiconductors

V. V. Enaldiev,
F. Ferreira,
V. I. Fal'ko

Abstract: Moiré structures in small-angle-twisted bilayers of two-dimensional (2D) semiconductors with a broken-symmetry interface form arrays of ferroelectric (FE) domains with periodically alternating out-of-plane polarization. Here, we propose a network theory for the tunability of such FE domain structure by applying an electric field perpendicular to the 2D crystal. Using multiscale analysis, we derive a fully parametrized string-theory-like description of the domain wall network (DWN) and show that it undergoes a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Applying this concept to a twisted bilayer, the stacking domains can be considered polar domains, where neighboring domains have opposite polarization. It has been suggested that the relative sizes of these domains can be tuned with the application of an electric field perpendicular to the bilayer, leading to a nonzero total polarization of the superlattice [10,11], which can be very nonlinear when the moiré period is large. Although experimental * db729@cantab.ac.uk measurements clearly show a ferroelectric response in homobilayers, from a theoretical perspective an ideal homo-bilayer has zero total polarization at zero field [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this concept to a twisted bilayer, the stacking domains can be considered polar domains, where neighboring domains have opposite polarization. It has been suggested that the relative sizes of these domains can be tuned with the application of an electric field perpendicular to the bilayer, leading to a nonzero total polarization of the superlattice [10,11], which can be very nonlinear when the moiré period is large. Although experimental * db729@cantab.ac.uk measurements clearly show a ferroelectric response in homobilayers, from a theoretical perspective an ideal homo-bilayer has zero total polarization at zero field [10].…”
Section: Introductionmentioning
confidence: 99%
“…Separate to the question of whether or not the overall system exhibits a ferroelectric response is the question of whether or not the stacking domains themselves are ferroelectric. Several theoretical studies have claimed, without any justification, that the stacking domains in homo-bilayers are ferroelectric [11][12][13]. This is simply incorrect: the domains are determined by the structure, and even if they change in area in response to an applied field, the orientation of the polarization in each domain is pinned cannot be inverted [10].…”
Section: Introductionmentioning
confidence: 99%